2012
DOI: 10.6000/1927-520x.2012.01.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Serum Profile of Thyroid Hormones from Birth to Puberty in Buffalo Calves and Heifers

Abstract: Growth is outcome of interactions among several factors, where thyroid hormones play a key role in coordination of these factors and the information of thyroid hormones in relation to growth in buffalo calves and heifers is not adequate. Thus the study was conducted on Murrah female buffalo calves and heifers, varying in age from newborn to 30 months. The study investigated the serum thyroid patterns in female Murrah buffalo calves and heifers from birth to puberty. The thyroid stimulating hormone concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
3
14
0
1
Order By: Relevance
“…The possible reason for such results might be due to antioxidant, vitamin C which is present in both herbal plants. Our findings are in agreement with the reports of Jain (2006) and Ingole et al (2012), who reported that, there was higher T 3 and T 4 concentration in 0-7 days old buffalo calves and there after the concentration decreased to lower values at 1-2 months as observed in our experimental findings.…”
Section: Growth Performancesupporting
confidence: 94%
“…The possible reason for such results might be due to antioxidant, vitamin C which is present in both herbal plants. Our findings are in agreement with the reports of Jain (2006) and Ingole et al (2012), who reported that, there was higher T 3 and T 4 concentration in 0-7 days old buffalo calves and there after the concentration decreased to lower values at 1-2 months as observed in our experimental findings.…”
Section: Growth Performancesupporting
confidence: 94%
“…The TH play a key role in co-ordination of different factors involved in growth, which is of great economic importance as far as the livestock enterprises are concerned [ 5 ]. TH directly influence growth by altering biochemical reactions; and being anabolic hormones, cause positive nitrogen balance and promote growth and development [ 5 ]. In the present study, the TSH levels were lowest in calves and increases among the heifer and the level decreases in the adult.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, TH is required for normal growth and development indicating a pivotal role in growth regulation. Since they are necessary for normal growth; optimal concentrations of TH act as growth stimulators [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…high levels of triiodothyronine and thyroxine at birth might be due to an early adaptation of the calf to the external environment. Ingole et al (2012) also reported significantly (P<0.01) higher values of thyroid hormones in zero to seven days old buffalo calves. The higher values of T 3 and T 4 in calves of G 1 might be due to effort of calves to adapt their metabolic balance to cold conditions.…”
Section: Cortisolmentioning
confidence: 78%